Biodiversity Genetic Conservation as a Key to Support Agro-Eco-Edu-Tourism Program in Southeast Asia - Johari, Shazali Bin; Rahmawati, Dewi (SEAMEO BIOTROP, 2023)
Biodiversity will be a long-term asset that needs to be studied sustainably for human welfare. Genetic diversity is the main pillar of species and ecosystem diversity. Genetic conservation is an effort to manage and conserve species using a molecular approach to understanding various aspects of species biology. The existence of biodiversity has various benefits. From a social perspective, biodiversity can be utilized for agro-edu education, recreation, and research facilities. Preservation of genetic diversity is an effort to support the agro-ecoedu-tourism program, which has many benefits, including pleasure from tourism activities and visitors' education about biodiversity. Changes in land use cause forest degradation, habitat loss or damage, resulting in loss of biodiversity. Mitigation of biodiversity management is needed to maintain the balance of ecosystems and environmental functions.